Kajian Yuridis terhadap Tindak Pidana Praktik Kedokteran Oleh WNA tanpa Surat Tanda Registrasi Sementara (Studi Kasus Putusan Pengadilan Negeri Jakarta Utara Nomor 450/Pid.Sus/2020/Pn_Jkt.Utr) - Seto Hanggoro Setiadji; Guanawan Nachrawi (FOCUS, 2026)
The increasing demand for health services and international cooperation has expanded opportunities for foreign national doctors to practice in Indonesia. Nevertheless, such practices must be regulated to ensure professional competence, patient safety, and legal certainty. This study analyzes the legal regulation on the obligation of Temporary Registration Certificates (Surat Tanda Registrasi Sementara/STR-S) for foreign doctors and examines judicial considerations in Decision Number 450/Pid.Sus/2020/PN Jkt.Utr. Using a normative juridical method with statutory and case approaches, the study finds that STR-S obligations are governed by Law Number 17 of 2023 on Health, Government Regulation Number 28 of 2024, Minister of Health Regulation Number 13 of 2025, and Indonesian Medical Council Regulation Number 17 of 2013. These regulations establish requirements, supervision, and limitations on medical practice by foreign doctors. Although the court correctly fulfilled the elements of the offense, the nine-month imprisonment imposed has not fully reflected the objectives of punishment considering the serious risks to patient safety. Therefore, stricter sanctions are necessary to strengthen deterrence and public trust in health law enforcement.